The Muslims of India: Policies and Practices - Tariq Hameed Bhatti (Journal of Political Studies, 2013)
The Indian Muslims have been facing serious setbacks since the independence despite the Indian government declared to have secular system. In many domains of life, the Indian Muslims are being deprived of their legal rights. Having profound percentage of the population, they played excellent role in divergent fields of life but their services are hardly appreciated by their governments.